Shortening Postoperative Stay after Parathyroidectomy - A District General Hospital Experience - Sinha, Sidhartha; Fok, Matthew; Ahmad, Ijaz; Al-Sheikh, Mustafa; Backhouse, Christopher (International Archives of Otorhinolaryngology, 2020)
Introduction Historically, concerns about complications following parathyroid surgery, such as airway compromise, bleeding and hypocalcemia, have precluded its consideration as a short-stay surgical procedure. Recent advancements in perioperative care have resulted in several publications demonstrating that parathyroidectomy can be safely performed as a short-stay procedure.Objectives The aim of the present study was to describe the process of implementing a short-stay protocol focusing on preoperative patient education and postoperative calcium management for those undergoing surgery for primary hyperparathyroidism (PHP).Method A retrospective audit of consecutive parathyroidectomies performed for PHP over the period between 2010 and 2013 was performed. A short-stay protocol (SSP) was introduced focusing on postoperative calcium management. Results were reaudited over the period between 2013 and 2015.Results Consecutive parathyroidectomies in 76 patients were included in the study. A total of 42 patients underwent parathyroidectomy prior to the introduction of the protocol. A total of 26.2% of these patients were symptomatic from hypercalcemia. A total of 40 out of 42 (95.2%) patients had a biochemical cure. A total of 36 out of 42 (85.7%) cases were due to parathyroid adenomas. A total of 34 patients underwent surgery following the introduction of the protocol. A total of 13 out of 34 (38.2%) of the patients had symptomatic hypercalcemia. A total of 33 out of 34 (97.1%) had a biochemical cure. A total of 32 out of 34 (94.1%) cases were due to parathyroid adenomas.The length of stay decreased from a median of 3 days (range 2–9 days; mean 3.32) preprotocol to a median of 2 days (range 2–3 days; mean 2.16) postprotocol (p < 0.0001) with no difference in the 30-day unplanned readmission rate (4.8 versus 2.9%; p = 0.999).Conclusions The postoperative length of stay after parathyroidectomy for PHP can be safely reduced through patient education and by rationalizing postoperative calcium management without adversely affecting outcomes.
Keywords: Parathyroidectomy; length of stay; surgical outcomes; quality improvement; endocrine; head and neck surgery; short stay surgery